2022
DOI: 10.1186/s13287-022-02757-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two cell-free therapeutics derived from adipose tissue: small extracellular vesicles versus conditioned medium

Abstract: Background Cell-free therapy has been inspired as a promising approach to overcome the limitations of traditional stem cell therapy. However, the therapeutic effect between extracellular vesicles and conditioned medium with the same source had not been compared. Our previous studies have shown that both the conditioned medium of adipose tissue (adipose tissue extract, ATE) and its further purification product small extracellular vesicles (sEV-AT) contributed to adipose tissue regeneration. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…In the past few years, we found sEV-AT could effectively induce adipose tissue regeneration ( Dai et al, 2017 ) and adipose tissue extract (ATE) also showed the same ability ( He et al, 2022 ). We also found the ability of sEV-AT derived from rats and porcine to repair soft tissue was similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few years, we found sEV-AT could effectively induce adipose tissue regeneration ( Dai et al, 2017 ) and adipose tissue extract (ATE) also showed the same ability ( He et al, 2022 ). We also found the ability of sEV-AT derived from rats and porcine to repair soft tissue was similar.…”
Section: Discussionmentioning
confidence: 99%
“…For tissue regeneration, sEVs have been reported to recruit host cells, regulate immune responses, stimulate angiogenesis, and promote tissue repair or regeneration ( Qi et al, 2016 ; Zhang et al, 2016 ; Ahn et al, 2018 ). Our previous study has shown that adipose tissue-derived small extracellular vesicles (sEV-AT), possessed the typical characteristics of sEVs, could effectively promote adipose tissue regeneration ( Dai et al, 2017 ; Dong et al, 2020 ; He et al, 2022 ). However, the interaction between sEV-AT and the host’s immune system, especially macrophages, was unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The particle size and size distribution of h-sEV-AT were determined by Zeta View analysis system (Particle Metrix, Germany) according to the manufacturer's protocol. The marker proteins were detected by Western blot according to our previous methods [13,16]. Briefly, 30 Îźg h-sEV-AT mixed with loading buffer (Solarbio, China), boiled for 10 min, resolved on 10% polyacrylamide gel, and blotted onto a nitrocellulose membrane.…”
Section: H-sev-at Isolation and Characterizationmentioning
confidence: 99%
“…Our previous study has shown that rat and porcine adipose tissue-derived small extracellular vesicles effectively promoted soft tissue regeneration [13][14][15][16]. However, whether small extracellular vesicles could be isolated from human liposuction adipose tissue and whether it also showed effectiveness on soft tissue were unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Adipose tissue, which is rich in cytokines, has been processed and applied in various diseases ( 22 , 23 ). Cell-free fat extract (CEFFE) is a cell-free liquid with active protein components acquired from adipose tissues via the process of mechanical emulsification and centrifugation to remove cellular debris and viable cell components and sterilization, which has advantages of an autogenous source, low immunogenicity, no tumorigenicity, high clinical safety, and low ethical risk.…”
Section: Introductionmentioning
confidence: 99%